Protease inhibitors exposure is not related to lung cancer risk in HIV smoker patients. (1st June 2015) - Bruyand, Mathias; Le Marec, Fabien; Lavole, Armelle; Leffondre, Karen; Spano, Jean Philippe; Le Moing, Vincent; Tattevin, Pierre; March, Laura; Cadranel, Jacques; Bonnet, Fabrice; Guiguet, Marguerite
<x xml:space="preserve">Abstract</x> Objective: We aimed at assessing in persons living with HIV with a smoking history an association between lung cancer risk and protease inhibitors exposure, especially ritonavir. Design: A nested case–control study was conducted within the ANRS CO4 FHDH, CO3 Aquitaine and Tenon's Hospital Cohorts. Methods: Cases and controls were eligible if they were ex-smokers or current smokers at the index date, and had a CD4+ cell count reported in the year preceding the index date. Cases were incident cases of lung cancer diagnosed between 1 January 2000 and 31 December 2011. All cancer cases were validated and histological types identified when available. Three controls were randomly selected by incidence density sampling using calendar time as the time axis, with individual matching on cohort, age (± 5 years), route of HIV acquisition, sex and hospital. Analyses were performed using conditional logistic regression adjusted for nadir CD4+ cell count and smoking status. Ritonavir and protease inhibitors exposures were represented in separate models using categorical variables (never exposed, ever exposed). Several sensitivity analyses were performed. Results: This study performed in 1447 persons living with HIV with a smoking history (383 lung cancer cases and 1064 control patients) did not evidence any association between lung cancer risk and protease inhibitors exposure including ritonavir. Conclusion: These results suggest that the risk of lung cancer is not influenced by pharmacologically induced P450 cytochrome protease inhibitors inhibition among smokers or ex-smokers.